Oral administration of Lacticaseibacillus rhamnosus HM126 alleviates DNFB-induced atopic dermatitis in BALB/c mice by modulating immunity, gut microbiota, and metabolites - Xie, Lili; Li, Xianping; Liu, Lu; Zhao, Junying; Luo, Lingling; Qiao, Weicang; Chen, Lijun (Frontiers in Immunology, 2025)
IntroductionProbiotics have emerged as a promising and safe alternative therapy for atopic dermatitis (AD) by regulating the gut microbiota-immune axis, correcting type 1/type 2 imbalance, and repairing the skin barrier.MethodsA mouse model of AD was established using diphenylnitromethane (DNFB). Low, medium, and high doses of human milk-derived Lacticaseibacillus rhamnosus HM126 were administered to investigate its effects on the model. We observed the scratching frequency and skin lesion scores after 28 days of continuous oral administration. Serum biochemical indicators and inflammatory cytokines were measured using ELISA, whereas the gut microbiota in feces was analyzed using 16S rDNA sequencing. Non-targeted metabolomics was used to assess the changes in fecal metabolites.Results and discussionCompared to the DNFB group, high-dose L. rhamnosus HM126 significantly reduced scratching frequency in AD mice. The low-dose group showed significantly reduced IgE levels. Additionally, the IFN-γ/IL-4 ratio significantly increased, indicating that L. rhamnosus HM126 modulates type 1/type 2 immune factors toward equilibrium. 16S rDNA analysis revealed that L. rhamnosus HM126 significantly reduced the ACE index and Chao 1 index of the gut microbiota in mice with AD, thereby reshaping the composition of the gut microbiome. Metabolomics analysis suggested that L. rhamnosus HM126 may improve AD by influencing the levels of asiatic acid, phytosphingosine, Ser-Glu, prostaglandin F2 alpha ethylamide (PGF(2α)EA), argininosuccinic acid, L-rhamnose, and gamma-L-glutamyl-L-glutamic acid. This study demonstrated that L. rhamnosus HM126 maintains the type 1/type 2 balance and effectively modifies the gut microbiota structure and metabolic changes to improve AD. Our findings provide a scientific basis for the development of probiotic therapeutics to prevent and treat this condition.